Pemberdayaan Moderasi Beragama Berbasis Kearifan Lokal dalam Memperkuat Kerukunan Umat Beragama di Kabupaten Pesawaran: Pendekatan Participatory Rural Apprasial (PRA) - Syukur, Abdul; Mubasit, Mubasit; Wuryan, Siti; Mustofa, Muhamad Bisri (AKM, 2025)
The empowerment of religious moderation based on local wisdom in Pujodadi Village, Negeri Katon District, Pesawaran Regency, is an important effort to strengthen religious harmony by utilizing traditions maintained for generations by the local community. There is a value of local wisdom in Lampung culture called the Pill Pesenggiri culture, which means upholding the values of dignity, dignity, and self-esteem in running the social system. The value of piil pesenggiri consists of four value terms: Juluk Adok, Nemui Nyimah, Sakai Sambayan, and Nengah Nyappur. The Participatory Rural Appraisal (PRA) approach is applied by identifying and utilizing community assets such as religious leaders, traditional leaders, places of worship, and local values to hold joint activities, develop tolerance education programs, and provide training to community leaders. Collaboration between various community groups, religions, cultures, governments, and related stakeholders is very important in this process. The main purpose of this service is to increase religious tolerance and harmony, strengthen community capacity in resolving conflicts, increase community participation, and preserve local wisdom as the foundation for harmony and tolerance between religious communities. With this approach, it is hoped that a more tolerant and harmonious society can be created in carrying out religious life, as well as ensuring the sustainability of religious moderation programs that have a positive impact on the local community.